2020
DOI: 10.3389/fmicb.2020.596914
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring tRNAs With Non-canonical Structures

Abstract: Transfer RNA (tRNA) is the central molecule in genetically encoded protein synthesis. Most tRNA species were found to be very similar in structure: the well-known cloverleaf secondary structure and L-shaped tertiary structure. Furthermore, the length of the acceptor arm, T-arm, and anticodon arm were found to be closely conserved. Later research discovered naturally occurring, active tRNAs that did not fit the established 'canonical' tRNA structure. This review discusses the non-canonical structures of some we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 115 publications
2
27
0
Order By: Relevance
“…We then analyzed other sncRNA categories where read lengths can be variable depending on how the RNA is processed. We found that reads aligned to tRNAs, which are ∼70 – 100 nt [37], had an average read length of 30 nt and a 90-precentile range of 28 – 31 nt ( Table 1 ). This result suggests that rat epididymosomes do not carry full length tRNAs, but rather carry either tRNA fragments (tRFs) or tRNA-halves, which are 14 – 30 nt and 30 – 40 nt in length respectively [38].…”
Section: Resultsmentioning
confidence: 99%
“…We then analyzed other sncRNA categories where read lengths can be variable depending on how the RNA is processed. We found that reads aligned to tRNAs, which are ∼70 – 100 nt [37], had an average read length of 30 nt and a 90-precentile range of 28 – 31 nt ( Table 1 ). This result suggests that rat epididymosomes do not carry full length tRNAs, but rather carry either tRNA fragments (tRFs) or tRNA-halves, which are 14 – 30 nt and 30 – 40 nt in length respectively [38].…”
Section: Resultsmentioning
confidence: 99%
“…Instead, in other bacteria, a deletion of a component of the transulfursome may lead many species of microorganisms to be auxotrophic for Cysteine due to their inability to synthesize it [ 28 , 29 ], resulting in a likely loss of information on specific tRNAs [ 26 ]. Recently, tRNA molecules with non-canonical structures have also been discovered [ 30 ]. These natural tRNA variants are, however, efficiently utilized during translation by the bacterial system and appear to be associated with functional interaction with enzymatic partners that is consistent with highly efficient evolutionary diversification of tRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…A second hypothesis would be that the degenerated tRNA entirely missing the TV-loop, which was detected using ARWEN, could be functional. However, although non-standard forms of mitochondrial tRNA can be found among metazoans (Krahn et al, 2020), they are rather scarce among protists (Gray et al, 1998). A third hypothesis would be that a functional tRNA-Trp(uca) is imported from the cytosol.…”
Section: A Complex Mitogenomementioning
confidence: 99%